Advances in single-cell sequencing technology in the field of hepatocellular carcinoma - Qin, Rongyi; Zhao, Haichao; He, Qizu; Li, Feng; Li, Yanjun; Zhao, Haoliang (Frontiers in Genetics, 2022)
Tumors are a class of diseases characterized by altered genetic information and uncontrolled growth. Sequencing technologies provides researchers with a better way to explore specific tumor pathogenesis. In recent years, single-cell sequencing technology has shone in tumor research, especially in the study of liver cancer, revealing phenomena that were unexplored by previous studies. Single-cell sequencing (SCS) is a technique for sequencing the cellular genome, transcriptome, epigenome, proteomics or metabolomics after dissociation of tissues into single cells. Compared with traditional bulk-sequencing, single-cell sequencing can dissect human tumors at single-cell resolution, finely delineate different cell types, and reveal the heterogeneity of tumor cells. In view of diverse pathological types and complex pathogenesis of hepatocellular carcinoma (HCC), the study of the heterogeneity among tumor cells can help improve its clinical diagnosis, treatment and prognostic judgment. On this basis, SCS has revolutionized our understanding of tumor heterogeneity, tumor immune microenvironment, and clonal evolution of tumor cells. This review summarizes the basic process and development of single-cell sequencing technology and its increasing role in the field of hepatocellular carcinoma.